Mastery of nature : promises and prospects - Minkov, Svetozar, 1975-; Trout, Bernhardt L.; Doneson, Daniel Adam (University of Pennsylvania Press, 2018)
Ranging from ancient Greek thought to contemporary quantum mechanics, Mastery of Nature investigates to what extent nature can be conquered to further human ends and to what extent such mastery is compatible with human flourishing.